2014
DOI: 10.1111/hsc.12172
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to developing diabetes self-management skills in a low-income sample in North Carolina, USA

Abstract: High rates of diabetes diagnosis and poor diabetes outcomes are particularly significant in low-income, socially disadvantaged populations. Although many social and economic predictors of poor self-management outcomes are known, few studies have examined how these elements impact the ability to develop self-management capacities in low-income populations. This article presents new insights into low-income women’s challenges and successes to becoming more adept self-managers. Interview data were collected in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…19 Promoting effective diabetes self-management has long been a challenging issue for the health systems, healthcare providers, community workers, and patients with diabetes. 20 Although the data regarding diabetes management for T2DM patients recovering from COVID-19 during isolation remain scarce, notably, previous studies have reported that among Chinese T2DM patients, only 22.76%-40.09% have achieved optimal glycemic control (hemoglobin A1c level<7.0%, 53 mmol/mol) [21][22][23] and 9.20%-16.43% have manifested good self-management behaviors. 21,24 This raises the issue of how to identify factors that hinder diabetes selfmanagement and to address these potential barriers.…”
Section: Introductionmentioning
confidence: 99%
“…19 Promoting effective diabetes self-management has long been a challenging issue for the health systems, healthcare providers, community workers, and patients with diabetes. 20 Although the data regarding diabetes management for T2DM patients recovering from COVID-19 during isolation remain scarce, notably, previous studies have reported that among Chinese T2DM patients, only 22.76%-40.09% have achieved optimal glycemic control (hemoglobin A1c level<7.0%, 53 mmol/mol) [21][22][23] and 9.20%-16.43% have manifested good self-management behaviors. 21,24 This raises the issue of how to identify factors that hinder diabetes selfmanagement and to address these potential barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The care includes lifestyle modification (eg, diet, physical activity, and weight management), glucose monitoring, prevention of complications, and multiple medication regimens [7,8]. Barriers to the effectiveness of diabetes care include insufficient knowledge and training that patients received [9], requiring permanent behavior change [10], financial burden [11], and complication-specific treatments [12]. Patient education and support by a multidisciplinary team of professionals (eg, physicians, nurses, dietitians, and psychotherapists) may help improve the quality of care [13], although they could be costly and unavailable in some developing countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Even under times of stress, habitual behaviors are more likely to be consistently engaged in than non-habitual behaviors as long as performance contexts remain relatively stable (Neal, Wood, & Drolet, 2013). Unstable or highly variable life context (e.g., shift work, sudden changes in employment or caregiving status) may significantly disrupt habit development (Fritz, 2014a).…”
Section: Habit In Everyday Lifementioning
confidence: 99%